Integration of a social domain in a manufacturing simulation software. (2016) - Widok, Andi H.; Wohlgemuth, Volker
This paper presents and discusses the technical development of a software component for the simulation of manufacturing entities. The component is intended to facilitate a social domain to the existing simulation software, which already integrates the classical, economical perspective as well as an environmental perspective through the inherent usage of material flow analysis (MFA) and life cycle assessment (LCA) combined in one modelling approach. The main aspects this paper addresses are, in that order, the motivation behind this approach, the main conceptual challenges for the development and the predispositions of the software. Furthermore, the key features of the actual implementation are presented and finally, the question is briefly discussed, whether this approach is worthwhile.